ANALISIS PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ45 - Gonawan, Steven Habel; Trihastuti, Adiati (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTCompetition in the business, making each company seeks to improve performance so that all the company's goals can be achieved. The main task of the company management is to determine the target capital structure which included a proportion of funding by the company's debts. One measure of success in the management of the company is profitability. LQ 45 group are a group of the company's shares that are of interest and concern to investors. The purpose of this study is determine significant influence partially and simultaneously company size and capital structure on profitability in LQ45 company. This research is causality using a quantitative approach. This study design using the design of quantitative research methods. This research was conducted in LQ45 companies listed on the Indonesia Stock Exchange, when the study was conducted in January-April, 2016. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange. The research sample used are LQ 45 companies on the Indonesia Stock Exchange 2011-2014 period. The sampling technique used is sampling non-probability. The sampling method in this study using purposive sampling method. Data were analyzed using linear regression. Based on the analysis, it can be concluded that the variable company size and its capital structure has a significant influence simultaneously and partially on profitability in the LQ45 company. It is known from the value of F (significance level) at t is smaller than ? (0.05). Keywords: company size, capital structure, profitability